Chinese American voices : from the gold rush to the present - Yung, Judy; Chang, Gordon H.; Lai, H. Mark (University of California Press, 2006)
Offering a textured history of the Chinese in America since their arrival during the California Gold Rush, this work includes letters, speeches, testimonies, oral histories, personal memoirs, poems, essays, and folksongs. It provides an insight into immigration, work, family and social life, and the longstanding fight for equality and inclusion.